Trade Liberalization and its Impact on Sri Lanka’s Regional Trade after 1977 - Mohamed Nufile, A.A. (My University, 2013)
This thesis examines a number of issues concerning the economic liberalization, free trade doctrine, regionalism and regional free trade areas (FTAs), with special reference to SAPT/SAFTA and also, this study attempts to estimate Sri Lanka’s bilateral trade activities with member countries of SAFTA, AFTA, NAFTA, and EFTA after the economic liberalization and the achievement of net trade advantages by Sri Lanka using the gravity model of trade. Panel data for the period 1980-2010 across thirty five countries is employed in the analysis. The main objectives of this research are to find out the trade relationship of Sri Lanka with partner countries especially SAARC countries and after the trade liberalization and the achievement of net trade advantages by Sri Lanka. The coefficients obtained from the model are used to predict the trade potential of partner countries worldwide as well as within specific SAARC region. The results expose that Sri Lanka’s existing trade potential with partner countries is high. Therefore, Sri Lanka should explore ways and means to further improve its trade relations with partner countries and also concentrate more on new products to increase its market share as far as possible. However, trade volume of Sri Lanka with partner countries is mixed despite the existing significant potentials. The main obstacles to this end are political, ethnic and social tensions in Sri Lanka as well as within intra and extra-region. Moreover, Sri Lanka faces several major challenges such as diminishing marginal returns to economic integration, importance of non-tariff barriers to trade, homogeneous products and still unsettled ethnic problems. It is pointed out that Sri Lankan Entrepreneurs and exporters need to diversify from traditional export markets to industrial markets worldwide. In addition to that, the results were clearly showed that trade liberalization helps more to Sri Lanka for its bilateral trade expansion or increase with SAARC member countries as well as AFTA, NAFTA and EU members. But, individually, the per capita GDP differs as larger among them. This implies that in Post- liberalized scenario Sri Lanka’s trade dependency ratios have increased compared to pre-liberalized scenario. Hence, Sri Lanka should encourage investors within the region as well as outside to invest in Sri Lanka. One important result of this study suggests that SAPTA/SAFTA has had an intra- bloc trade growing effects from 1996 and more exciting from 2004. This implies that trade among members of SAPT/SAFTA has increasing effect. Meanwhile, AFTA, NAFT.A, EFTA have had an ‘open trading bloc’ and also growing effects during the study period. Suggested, the finding of this study also advocates that SAFTA/SAFTA essentially creates rather than diverts trade. As Sri Lanka has been able to make significant gains from intra-regional trade with SAARC countries and also with rest of the world, it is advisable that Sri Lanka reduces or eliminates all trade and non-trade barriers simultaneously with due caution. Further, the economic freedom index was not acceptable position as worldwide norms in Sri Lanka. Finally, therefore, it should be highly maintained in all the elements of Index of Economic Freedom and gets benefits in future.